A combined natural supplement lowers LDL cholesterol in subjects with moderate untreated hypercholesterolemia: a randomized placebo-controlled trial. (November 2013) - Barrat, Emmanuel; Zaïr, Yassine; Ogier, Nicolas; Housez, Béatrice; Vergara, Coralie; Maudet, Corinne; Lescuyer, Jean-François; Bard, Jean-Marie; Carpentier, Yvon A.; Cazaubiel, Murielle; Peltier, Sébastien L.
Abstract Objective: To investigate the effect of a natural cholesterol-lowering supplement (NCLS) containing red yeast rice, policosanols and artichoke leaf extracts on blood lipid concentrations as well as on safety parameters when given over 16 weeks in 100 volunteers with untreated moderate hypercholesterolemia, in a randomized, double-blind, placebo-controlled trial. Results: Reduction of primary outcome low-density lipoprotein cholesterol [−0.22 g/L (95% confidence interval, CI: −0.31 to −0.12) corresponding to −14.3% from baseline (95% CI: −21.5 to −7.2) compared to placebo], as well as total cholesterol, apolipoprotein B100 and apolipoprotein B100/apolipoprotein A-I ratio, were observed after 16 weeks of supplementation with NCLS. These effects were already observed at Week 4 and 10 of supplementation. No significant changes were observed in high-density lipoprotein, triacylglycerol, creatine kinase, lactate dehydrogenase and coenzyme Q10 levels, as well as in markers of liver and renal function. Conclusions: The NCLS was effective in reducing low-density lipoprotein cholesterol and apolipoprotein B100 in subjects with moderate hypercholesterolemia, without modifying safety parameters.